2014
DOI: 10.1097/ajp.0b013e318285d1ba
|View full text |Cite
|
Sign up to set email alerts
|

Topical Treatment of Neuropathic Pain Using Compounded Medications

Abstract: This article discusses the role of topical medications in treating localized cutaneous NP and the role of the compounding pharmacists in applying this therapeutic approach (eg, the scientific considerations that the pharmacist should take into account).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 28 publications
0
43
0
1
Order By: Relevance
“…However, for patients with multiple medical problems, these topical treatments may be of some benefit because of reduced drug interactions. 82 Non-pharmacologic treatments Two non-randomized studies with a before and after design found that exercise improved pain in pre-diabetic neuropathy and diabetic sensorimotor polyneuropathy as well as improving nerve fiber density on skin biopsy. 83 84 However, because these studies were not all blinded the optimum exercise routine is yet to be determined.…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…However, for patients with multiple medical problems, these topical treatments may be of some benefit because of reduced drug interactions. 82 Non-pharmacologic treatments Two non-randomized studies with a before and after design found that exercise improved pain in pre-diabetic neuropathy and diabetic sensorimotor polyneuropathy as well as improving nerve fiber density on skin biopsy. 83 84 However, because these studies were not all blinded the optimum exercise routine is yet to be determined.…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…To penetrate both the outermost layer of the skin, the stratum corneum, and the epidermis, the compounded drug should have both hydrophobic and hydrophilic properties (reviewed in [14]). Because the drug's potential therapeutic effect hinges, in part, on its ability to be absorbed, flux serves as an indicator of a compounded product's quality.…”
Section: Discussionmentioning
confidence: 99%
“…The skin is an important target for treatments aimed at pain management as several studies have demonstrated the presence of receptors and ligands on peripheral nociceptors and non-neural cells, as well as signaling between neural and non-neural skin cells (reviewed in [14]). Several studies have demonstrated that the use of compounded transdermal analgesics leads to high drug concentrations at the target site while maintaining low systemic drug levels, leading to decreased systemic side effects (reviewed in [15]).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some topical treatments have already been mentioned in several guidelines for the pharmacological treatment of NP, as well as in clinical reports, along with more traditional systemic treatments [5••, 610] as a stand-alone treatment or as an add-on therapy [11•]. Currently, the treatment of NP can include either systemic or localized therapies, with localized treatments associated with relatively fewer systemic side effects and drug–drug interactions and satisfactory efficacy [1214]. …”
Section: Introductionmentioning
confidence: 99%